3D printing in the battle against COVID-19 - Aydin, Ayca; Demirtas, Zeynep; Ok, Merve; Erkus, Huseyin; Cebi, Gizem; Uysal, Ebru; Gunduz, Oguzhan; Ustundag, Cem Bulent (SPRINGERNATURE, 2021)
Coronavirus disease 2019 (COVID-19) that is SARS-CoV-2, previously called 2019-nCoV, is a kind of human infectious disease caused by severe acute respiratory syndrome coronavirus. Based on the prompt increase of human infection rate, COVID-19 outbreak was distinguished as a pandemic by the World Health Organization (WHO). By 2020, COVID-19 becomes a major health problem all around the world. Due to the battle against COVID-19, there are some adversities that are encountered with. The most significant difficulty is the lack of equipment for the COVID-19 battle. Lately, there is not sufficient personal protective equipment (PPE) for hospital workers on the front lines in this terrifying time. All around the world, hospitals are overwhelmed by the volume of patients and the lack of personal protective equipment including face masks, gloves, eye protection and clothing. In addition, the lack of nasal swabs, which are necessary components, that are used for testing is another issue that is being faced. There are a small number of respirators, which are emergency devices that help patients breathe for a short period of time. To overcome the limited number of equipment available, the foremost solution can be 3D printing that allows three-dimensional renderings to be realized as physical objects with the use of a printer and that revolutionized prototyping. Low-cost desktop 3D printers allow economical 3D models and guides but have less quality approvals. 3D printing is already well integrated into the process of COVID-19 battle by manufacturing the equipment that are convenient. The goals of this review are to explore the techniques of 3D printing for the equipment that are used for COVID-19 battle and evaluate the materials that are used for manufacturing and the manufactured equipment. Lastly, the advantages and disadvantages of 3D printing are figured out.
Keywords: COVID-19; SARS-CoV-2; 3D printing; Biomaterials; Tissue engineering; FACE SHIELDS; TECHNOLOGY; DENTISTRY; MASKS; Materials Science